Flowers and foliage - a blooming market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Flowers and foliage are increasingly important exports from many ACP countries to the EC, United States and Canada. Despite the highly perishable nature of these products, and the long distance from their markets, tropical countries have gained a...